Assessing the Role of Sector Growth on Poverty and Inequality In Indonesia - Mela Yunita (FEB Universitas Sultan Ageng Tirtayasa, 2025)
Various economic sectors play different roles in reducing or exacerbating inequality and poverty, depending on their contribution to inclusive growth and job creation. This study analyzes the role of the agricultural, industrial, and services sectors in influencing poverty and inequality levels in Indonesia, using a case study of the Covid-19 period. This study aims to analyze the role of the agricultural, industrial, and service sectors in decreasing inequality and poverty, as well as comparing them in the pre COVID-19 period. This study tries to apply GMM panel estimation to 25 provinces in Indonesia during 2017-2021. The services sector shows the greatest influence on poverty and inequality then followed by the agricultural sector and industrial sector in the pre COVID-19 period. Meanwhile, during COVID-19, the industrial sector tends to increase poverty and inequality. However, the service sector doesn’t affect poverty and inequality during COVID-19. On the other hand, the agricultural sector has shown an important role in reducing inequality and poverty during the COVID-19. The results of this study confirm the important role of the agricultural sector during the COVID-19. In addition, this study shows the better role of fiscal policy in reducing inequality and poverty compared to monetary policy.